PENGARUH GULMA TERHADAP KOMPONEN FISIOLOGI BEBERAPA KULTIVAR KEDELAI (Glycine max (L.) Merr.) - Doni Hariandi; Didik Indradewa; Prapto Yudono (Jurnal Agroekoteknologi, 2019)
ABSTRACTThe research aims to identify the effects of weed on the physiology components ofsoybean cultivars. This field research is arranged using spit plot with three blocksas the repetition where the main-plot is the weed treatments and those are weedfree, weeding in a critical period, and weedy. Sub-plot is the soybean cultivarswhich are Anjasmoro, Argomulyo, Burangrang, Gema, Gepak Kuning, Kaba, andWilis. The research’s result show the weed treatments would effect no significantdifference in the chlorophyll content, rate of photosynthesis, and carbon dioxide onleaf parameters.